No Jim Crow church : the origins of South Carolina's Baha'i community - Venters, Louis (Gainesville : University Press of Florida, 2015)
Venters recounts the unlikely emergence of a cohesive interracial fellowship in South Carolina over the course of the twentieth century, as blacks and whites joined the Baha'i faith and rejected the region's religious and social restrictions.
First contacts, 1898-1916 -- The divine plan, the great war, and progressive-era racial politics, 1914-1921 -- Building a Baha'i community in Augusta and North Augusta, 1911-1939 -- The great depression, the second World War, and the first seven year plan, 1935-1945 -- Postwar opportunities, cold war challenges, and the second seven year plan, 1944-1953 -- The ten year plan and the fall of Jim Crow, 1950-1965 -- Coda: toward a Baha'i mass movement, 1965-1968.
Includes bibliographical references and index.
Print version record.
English.
Master record variable field(s) change: 072
Keywords: Bahai Faith -- South Carolina -- History -- 20th century; Bahais -- South Carolina; Race relations -- Religious aspects -- Bahai Faith -- History -- 20th century; South Carolina -- History; South Carolina -- Race relations -- History -- 20th century; RELIGION -- Islam -- General; Race relations -- Religious aspects -- Bahai Faith; Race relations; Bahai Faith; Bahais; South Carolina; HISTORY / United States / State & Local / South (AL, AR, FL, GA, KY, LA, MS, NC, SC, TN, VA, WV); 1900-1999; Electronic books; History